Teaching to Survive: Keeping Black Girls and Black Girlhood Studies on Campus. Issue 3 (1st December 2022) - Owens, Tammy C.
Abstract: It has been a hard-fought battle to secure Black Girlhood Studies as an essential college course that examines Black experiences of American childhood. To ensure its survivability, I argue that scholars must establish many homes for Black Girlhood Studies beyond Gender Studies and Black Studies departments. Further, given the illegibility of Black girls as youthful or innocent children, scholars must advocate for Black Girlhood Studies as a college course in academic departments or programs in which Black girls are potentially subjects of faculty or student research. I draw on my experiences teaching Black Girlhood Studies as a Black woman professor and ground my analysis in Black feminist conversations that emerged during the twentieth century to solidify Black Women's Studies in the academy.